Adolescent Pregnancy Counseling on Reproductive Health in the New Village of Ladang Bambu in 2021 - Suriati Lubis; Dwi Ris Hasanah (Institute of Computer Science (IOCS), 2021)
The purpose of this study was to provide knowledge to adolescents, especially young women, about reproductive health to prevent unwanted teenage pregnancies. And the activities carried out are to increase the knowledge of young women about reproductive health to prevent unwanted teenage pregnancies. Help prevent teenage pregnancies that result in dropping out of school, unprepared economic problems, teenage pregnancies under the age of 20 which are at risk for premature birth and increase maternal mortality. The types and forms of activities of this activity are as follows: providing material to young women about reproductive health to prevent unwanted teenage pregnancies. The results of the study are to achieve the objectives of the above activities,